Energy Transition and Regional Heterogeneity of Environmental Taxation in China: From the Perspective of Emission Reduction Effects - Xu, Yudan; Chen, Pinghua (Frontiers in Environmental Science, 2022)
It is commonly believed that the imposition of environmental taxation has the policy effect of reducing environmental pollution emissions. Thus, this paper examines the pollution reduction effects and regional heterogeneity of environmental taxation based on panel data of 30 provincial administrative regions in China. It is found that the current environmental taxation in China can promote the reduction of pollutant emissions to a certain extent, but the effect on individual pollutants is not outstanding; from the results of the regional heterogeneity test, there are differences in the effect of environmental taxation on the reduction of major pollutants in each region. And China's current environmental tax policy has a relatively strong effect on emission reduction in the western region with little effect in the eastern and central regions. Therefore, to better utilize the policy, this paper suggests adjusting the environmental tax levy standard according to local conditions and strictly levying environmental taxes and fees on various pollutants in terms of quantity.